Thermal image resolution on angular emissivity measurements using infrared thermography - Nunak, T.; Rakrueangdet, K.; Nunak, N.; Suesut, T. (My University, 2015)
This paper reports the effect of viewing angle and thermal image resolution (IFOV and FOV) of Thermal Imager (TI) on the emissivity, with a view to providing a potential temperature monitoring of equipment in the electrical power distribution system which the reliability of system is the most important concern. The results show that the emissivity, which is the most important parameter to obtain the accurate temperature, is approximately constant at the viewing angle less than 45°. In case of the changing of the object to detector distance, this will not affect to the temperature measurement if MFOV at the object level is smaller than the targeted object. This can be concluded that TI is an effective tool to measure the temperature and monitor the failure of electrical equipment installed in the position at far away from the operator.
Keywords: Electrical equipment; Emissivity measurements; Thermal image resolution; Thermal imager; Viewing angle